2022
DOI: 10.1177/00469580221133217
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Access to Palliative Care in Colombia: A Social Mapping Approach Involving Stakeholder Participation

Abstract: This study aimed to identify barriers to access to palliative care through a social mapping approach. In Colombia, the barriers to access to palliative care denote an enormous geographic disparity of resources and health needs, making it necessary to conduct community-based participatory research using an approach such as social mapping. A qualitative research design was used. Stakeholders from health insurance companies, regulatory authorities, regional health secretariats, health care professionals, patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…However, the study showed a lack of access to services, and all patients have to travel to Bogotá to receive palliative care. In this sense, these findings confirm what was reported by authors Vargas-Escobar Lina et al 15 on the problems of access to palliative care by patients and families in different regions of Colombia. 16 The family members in the study reported feelings of uncertainty and physical and emotional exhaustion.…”
Section: Discussionsupporting
confidence: 92%
“…However, the study showed a lack of access to services, and all patients have to travel to Bogotá to receive palliative care. In this sense, these findings confirm what was reported by authors Vargas-Escobar Lina et al 15 on the problems of access to palliative care by patients and families in different regions of Colombia. 16 The family members in the study reported feelings of uncertainty and physical and emotional exhaustion.…”
Section: Discussionsupporting
confidence: 92%
“…Una perspectiva cualitativa del problema deja ver como existe una marcada tendencia a considerar una baja relación entre las políticas públicas y los efectos en servicios y educación 18 . Los participantes consideran en los siete nodos evaluados como el consumo de opioides ha mejorado de manera significativa por la acción de las políticas establecidas en esta materia.…”
Section: Discussionunclassified
“…The qualitative data were analyzed using a content analysis method, and the findings are reported in a previous publication that maps stakeholders’ viewpoints on barriers for each dimension and regional node under study. 26 The interviews were recorded and transcribed in MS Word. Data saturation for each node was reached when the stakeholders did not provide new information that would contribute to identifying more perception of needs and resources in the regional nodes.…”
Section: Methodsmentioning
confidence: 99%